ECOSOC, As It Could Be - Christensen, Hanne (Advances in Social Sciences Research Journal, 2023)
This article outlines the intentions of the UN charter with ECOSOC, one of five charter-based organs of the United Nations. It suggests how they can be fulfilled in its endeavor to develop macro-social and macro-economic strategies beneficial for the entire UN membership for the General Assembly to adopt. Hence, to discuss the world population's economic and social livelihood conditions with member-states sharing memorable constructive experiences so that every member-state can duplicate what works to improve people´s livelihood. The potential of ECOSOC in this regard may not yet be fully explored, but holds a promising outcome that does not lead to conflict; on the contrary, it leads to cooperation and peaceful co-existence. And that is essentially what the United Nations is about. ECOSOC is an essential engine for that travel.